2004
DOI: 10.3390/91201100
|View full text |Cite
|
Sign up to set email alerts
|

Atom, Atom-Type, and Total Linear Indices of the “Molecular Pseudograph’s Atom Adjacency Matrix”: Application to QSPR/QSAR Studies of Organic Compounds

Abstract: Abstract:In this paper we describe the application in QSPR/QSAR studies of a new group of molecular descriptors: atom, atom-type and total linear indices of the molecular pseudograph's atom adjacency matrix. These novel molecular descriptors were used for the prediction of boiling point and partition coefficient (log P), specific rate constant (log k), and antibacterial activity of 28 alkyl-alcohols and 34 derivatives of 2-furylethylenes, respectively. For this purpose two quantitative models were obtained to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Through this experience, we have come to have interest in applying the model to a broader exploration of structure-permeability relationships [2]. Quantitative structure-permeability relationships (QSPRs) of the intestinal permeability across Caco-2 cells monolayer have been studied by many researchers [1,3]. The theoretical approach appears to be good to predict the human absorption of new drug candidates obtained by combinatorial chemistry methodologies, avoiding significant failure in late stage of the drug-discovery process.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Through this experience, we have come to have interest in applying the model to a broader exploration of structure-permeability relationships [2]. Quantitative structure-permeability relationships (QSPRs) of the intestinal permeability across Caco-2 cells monolayer have been studied by many researchers [1,3]. The theoretical approach appears to be good to predict the human absorption of new drug candidates obtained by combinatorial chemistry methodologies, avoiding significant failure in late stage of the drug-discovery process.…”
Section: Introductionmentioning
confidence: 97%
“…The estimation of human oral absorption of new drug candidates in the early stage of the drug discovery process is a useful tool in the lead-compound selection [1]. Several in vitro approaches, based on cell cultures, were used in this area over the last few years.…”
Section: Introductionmentioning
confidence: 99%
“…The calculated R 2 is 0.962; which reveal an equitable fitness as well as the efficacy of the model as shown in equation 3. Also, the calculated CV.R 2 was 0.999 {(> 0.5) (standard)} (Ponce et al 2004) and this showed the reliability and acceptability of the model as well as the adjusted R 2 with 0.823 which is greater than 0.6 (standard). Thus, the QSAR model would be predictive.…”
Section: Qsar Model Validationmentioning
confidence: 71%
“…The obtained value for fitting factor (R 2 ) (0.998) showed that it fitted well. Also, the cross validation value (CV.R 2 ) (0.998) showed the steadfastness of the developed QSAR model, because the value obtained was higher than 0.5 (Standard) (Ponce et al 2004). More so, the calculated value for adjusted R 2 (0.988) exposed that the QSAR model is prognostic since the calculated value is greater than 0.6 (Standard) ( Table 2).…”
Section: Qsar Studiesmentioning
confidence: 96%